FUT8-AS1 Inhibits the Malignancy of Melanoma Through Promoting miR-145-5p Biogenesis and Suppressing NRAS/MAPK Signaling - Chen, Xiang-jun; Liu, Sha; Han, Dong-mei; Han, De-zhi; Sun, Wei-jing; Zhao, Xiao-chun; Liang, Jun-qing; Yu, Li (Frontiers in Oncology, 2021)
Melanoma is the major lethal skin malignancy. However, the critical molecular drivers governing melanoma progression and prognosis are still not clear. By analyzing The Cancer Genome Atlas (TCGA) data, we identified FUT8-AS1 as a prognosis-related long non-coding RNA (lncRNA) in melanoma. We further confirmed that FUT8-AS1 is downregulated in melanoma. Reduced expression of FUT8-AS1 is correlated with aggressive clinical factors and inferior overall survival. Using in vitro functional assays, our findings demonstrated that ectopic expression of FUT8-AS1 represses melanoma cell proliferation, migration, and invasion. FUT8-AS1 silencing promotes melanoma cell proliferation, migration, and invasion. Furthermore, in vivo functional assays demonstrated that FUT8-AS1 represses melanoma growth and metastasis. Mechanistically, FUT8-AS1 was found to bind NF90, repress the interaction between NF90 and primary miR-145 (pri-miR-145), relieve the repressive roles of NF90 on mature miR-145-5p biogenesis, and thus promote miR-145-5p biogenesis and upregulate mature miR-145-5p level. The expression of FUT8-AS1 is positively correlated with miR-145-5p in melanoma tissues. Via upregulating miR-145-5p, FUT8-AS1 reduces the expression of NRAS, a target of miR-145-5. FUT8-AS1 further represses MAPK signaling via downregulating NRAS. Functional rescue assays demonstrated that inhibition of miR-145-5p reverses the tumor suppressive roles of FUT8-AS1 in melanoma. The oncogenic roles of FUT8-AS1 silencing are also blocked by MAPK signaling inhibitor MEK162. In conclusion, these findings demonstrate that FUT8-AS1 exerts tumor suppressive roles in melanoma via regulating NF90/miR-145-5p/NRAS/MAPK signaling axis. Targeting FUT8-AS1 and its downstream molecular signaling axis represent promising therapeutic strategies for melanoma.